Effect of Statins on Liver Enzymes and Lipid Profiles in Patients with Hyperlipidemia: A Biochemical and Physiological Perspective - Jalal Khan, Syeda Tahira Zaidi, Syed Azhar Hussain Zaidi, Muhammad Zarrar Arif ButtIrfan Ahmad, Ambreen Anjum, Farah Naz Tahir, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Hyperlipidemia is a significant risk factor for cardiovascular diseases, necessitating effective lipidlowering strategies. Statins, as HMG-CoA reductase inhibitors, are widely prescribed for thispurpose. However, concerns regarding their impact on liver enzymes persist. This study aimed toevaluate the effects of statin therapy on liver function tests and lipid profiles in hyperlipidemicpatients.